Discourse On Translation Involving The Malay Language. - Haroon, Haslina (2009)

(untitled)
Discourse on translation is taken to mean any text which expresses the writer's views and thoughts on translation, which may include methods and principles of translation. Although discourse on translation is a key component in the Malay translation tradition, this aspect of translation has received very little attention in discussion on the history of translation involving the Malay language.